Lessons from a dark time and other essays - Hochschild, Adam (University of California Press, 2018)
"This book collects some two dozen pieces from bestselling author Adam Hochschild, written over the past 25 years. All have been published before, most in the New York Review of Books but also in the New Yorker, Harper's, Mother Jones, and elsewhere. They are a mixture of essays about books, authors, one film, and the writing of history and on-the-ground journalism based on reporting from India, Africa, and elsewhere"--Provided by publisher.